2016
DOI: 10.1080/16506073.2016.1244559
|View full text |Cite
|
Sign up to set email alerts
|

Associations between lower order anxiety sensitivity dimensions and DSM-5 posttraumatic stress disorder symptoms

Abstract: Anxiety sensitivity (AS), a well-established individual difference variable reflecting a tendency to fear bodily sensations associated with arousal, has been implicated in the development and maintenance of posttraumatic stress disorder (PTSD). Despite these associations, little research has examined the relations between AS subfactors (eg physical, cognitive, and social) and PTSD symptoms and none have examined these associations in the context of DSM-5 (Diagnostic Statistical Manual of Mental Disorders, Fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 43 publications
5
30
2
Order By: Relevance
“…Indeed, a breadth of literature supports the link between AS and PTSS across a variety of study designs (see Olatunji & Wolitzky-Taylor, 2009 for a review). For instance, greater AS has been cross-sectionally associated with greater PTSS among police officers (Asmundson & Stapleton, 2008), community outpatients (Albanese et al, in press), non-treatment seeking community adults (Vujanovic, Zvolensky, & Bernstein, 2008), treatment-seeking veterans (Raines et al, 2017), and adults with substance abuse (McDermott, Tull, Gratz, Daughters, & Lejuez, 2009). Moreover, AS has been shown to predict PTSS longitudinally when assessed after a trauma (Marshall, Miles, & Stewart, 2010) and prospectively when AS is measured prior to a trauma (Boffa et al, 2016), thereby fitting the definition of a true risk factor (Kraemer et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a breadth of literature supports the link between AS and PTSS across a variety of study designs (see Olatunji & Wolitzky-Taylor, 2009 for a review). For instance, greater AS has been cross-sectionally associated with greater PTSS among police officers (Asmundson & Stapleton, 2008), community outpatients (Albanese et al, in press), non-treatment seeking community adults (Vujanovic, Zvolensky, & Bernstein, 2008), treatment-seeking veterans (Raines et al, 2017), and adults with substance abuse (McDermott, Tull, Gratz, Daughters, & Lejuez, 2009). Moreover, AS has been shown to predict PTSS longitudinally when assessed after a trauma (Marshall, Miles, & Stewart, 2010) and prospectively when AS is measured prior to a trauma (Boffa et al, 2016), thereby fitting the definition of a true risk factor (Kraemer et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some studies have identified certain factors of AS, such as cognitive concerns, to be particularly important in predicting PTSS (Raines et al, 2017). Second, although the 6 weeks of follow-up met the 1-month DSM-5 criteria for a PTSD diagnosis, and represents a key period of PTSS development, the follow-up period in the present study was relatively brief.…”
Section: Discussionmentioning
confidence: 70%
“…However, rates of developing PTSD in college-aged students are similar to the general population (Read et al., 2014). Despite the existence of efficacious treatments for PTSD, approximately one-third of people diagnosed still exhibit symptoms after treatment (Raines et al., 2017). Thus, it is vital to identify underlying factors that may be associated with the maintenance of PTSD symptoms to improve treatment efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety sensitivity includes three different facets; anxiety sensitivity physical concerns (ASPC), anxiety sensitivity cognitive concerns (ASCC), and anxiety sensitivity social concerns (ASSC; Taylor et al., 2007). Those with high AS fear the negative consequences of the physical (e.g., “It scares me when my heart beats rapidly”), cognitive (e.g., “I feel like I might be losing my mind or going crazy”), and social (e.g., “I worry that other people will notice my anxiety”) symptoms of anxiety (Raines et al., 2017; Taylor et al., 2007). Initially, AS was referenced specifically in the context of panic disorder; however, recent longitudinal research has indicated that PTSD symptoms and AS might have a bidirectional relationship (Marshall et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation